EVALUASI IMPLEMENTASI KEBIJAKAN RECREDENTIALING RUMAH SAKIT UMUM DAERAH ANUGERAH SEBAGAI MITRA BPJS KESEHATAN DI KOTA TOMOHON - Ere, Arfan La; Ilyas, Muh.; Montolalu, Freddy Chandra (JURNAL ILMIAH KESEHATAN MANADO, 2024)
The Indonesian government has created a health insurance system for the public known as the National Health Insurance Program (JKN Program). Hospitals must go through a recredentialing process to maintain their partnership with BPJS Kesehatan. Objective: This study aims to evaluate the implementation of the recredentialing policy in BPJS Kesehatan partner hospitals in Tomohon City using the health policy triangle theory. Method: This research uses a qualitative descriptive research method, with data collected from interviews, document reviews, and documentation. Results: The research results indicate that actors, content, context, and health policy processes influence the implementation of the recredentialing policy in BPJS Kesehatan partner hospitals in Tomohon City. Conclusion: The implementation of the recredentialing policy for RSUD Anugerah Kota Tomohon runs smoothly every year, although there are still some challenges in the preparation and implementation process. The involved parties are expected to coordinate and evaluate the previous recredentialing period's implementation, especially regarding scheduling, technical implementation, additional requirements, and cooperation period.